Imunoexpressão das proteínas APE-1 e XRCC-1 em carcinoma epidermoide de língua oral - Conceição, Thalita Santana (2016)
DNA repair systems play a critical role in protecting the human genome from damage caused by carcinogens present in the environment. Mutations in DNA repair genes may be responsible for tumor development and resistance of malignant cells to chemotherapeutic agents. The major pathway for oxidative DNA damage repair is the base excision repair pathway. The objective of this study was to investigate the immunoexpression of APE-1 and XRCC-1, which are proteins involved in DNA base excision repair and its association with clinical and histopathological parameters in oral tongue squamous cell carcinoma (OTSCC), in order to investigate a possible prognostic value for those proteins. The expression of APE-1 and XRCC-1 was evaluated semi-quantitatively by immunohistochemistry in 50 OTSCC cases. Clinical data was collected from patients’ medical charts and histopathological grading was performed for each case. Statistical analysis (Chi-square and Fisher’s exact tests; significance of 5%) was performed to determine the association between protein expressions and clinico-pathological characteristics. APE-1 was highly expressed in nucleus and cytoplasm in 56% of cases. XRCC-1 showed overexpression only in nucleus in 60% of cases. High expression of XRCC-1 was significantly associated to clinical stages I and II (P=0.02). Both proteins were not associated to other clinical parameters or histopathological grading. Our findings demonstrate that DNA base excision repair proteins APE-1 and XRCC-1 are upregulated in OTSCC, however, they are not related to clinical and histologic parameters, except for XRCC-1 association to better clinical staging. Our results indicate that the immunohistochemical expression of these proteins has no association with prognostic parameters in this tumor.